1997
DOI: 10.1046/j.1365-2168.1997.02464.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns and surgical results in adenocarcinoma of the oesophagus

Abstract: Recent improvement of results reflects patient selection, increased prevalence of early tumours, and dramatic reduction of the risks from oesophagectomy. New therapeutic directions should be investigated for locally advanced tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 28 publications
(2 reference statements)
3
24
0
Order By: Relevance
“…Most of the recent series report an operative mortality of 7% to 13% [10,13,15,16]. The overall operative mortality in the present study is 6.3%.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Most of the recent series report an operative mortality of 7% to 13% [10,13,15,16]. The overall operative mortality in the present study is 6.3%.…”
Section: Discussionsupporting
confidence: 51%
“…One study [10] reported T stage to be the main independent predictor of survival on multivariate analysis. The difference was statistically significant, however, only in T2 versus T4 patients and T3 versus T4 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of esophageal adenocarcinoma is increasing at an alarming rate in the Western societies [22]. The identification of factors contributing to cancer development may play a major role in defining a population at risk and in devising preventive strategies [4,5,10].…”
Section: Discussionmentioning
confidence: 99%
“…The only current reliable means of detecting dysplasia is endoscopy and biopsy [75,82] and the most widely accepted biopsy protocol is to take samples from each quadrant of the metaplastic segment at 1-or 2-cm intervals [83]. Surveillance endoscopy can subsequently be undertaken to attempt to detect dysplasia and early cancer [75], as some studies have demonstrated that patients presenting with cancer in surveillance programs have their tumours detected at an earlier stage [84][85][86][87][88][89] and have improved survival over patients diagnosed clinically (outside of surveillance programmes) [84][85][86][87][88][89][90][91]. The detection of high-grade dysplasia will also allow consideration to be given to radical therapy to attempt to cure adenocarcinoma prior to its development or spread [50, [91][92][93][94][95][96], localised treatment to ablate the metaplastic mucosa [97][98][99] or to perform a localised resection [100], as an oesophageal resection is associated with a risk of significant morbidity and occasional mortality [50, 91,92].…”
Section: Introductionmentioning
confidence: 99%